Beginning SharePoint communication sites : understanding and managing modern SharePoint online - Waghmare, Charles David (Office Essentials collection, 2023)
Understand SharePoint communication sites and create one on your own using SharePoint Home, available in Microsoft 365. This revised edition covers the new features in SharePoint communication sites and demonstrate how to effectively use them. You will also learn how to create a digital experience using SharePoint communication sites. This updated edition includes a new chapter on information management and governance, along with new topics such as seamless integration between Teams, using Power Automate and SharePoint Communication sites in tandem, and performing project and operations management activities with communication sites. Author Charles Waghmare starts by walking you through SharePoint communication sites and how to create them. Next, you'll explore various use cases to understand the benefits of communicating through SharePoint communication sites. Further, you will learn collaborative applications like Teams and its integration with SharePoint, followed by details of compliance and governance . You will then integrate communication sites with Microsoft 365 products for better end user collaboration. Finally, you will discover how to perform your day-to-day operations tasks using communication sites. After reading this book, you will be able to create and manage SharePoint communication sites and improve ways to communicate and collaborate within your organization.